Imogen : the mother of modernism and three boys - Novesky, Amy (Cameron + Company, 2012)
"Imogen's family didn't have much, and life was hard atop the wild hill they called home. But when Imogen declared she wanted to be a photographer, her father built a darkroom just for her. Flash forward. Imogen is a photographer and a mother. She has her hands full! How does she do it all? She turns the garden into a wonderland for her three growing boys and a workshop for herself. While she works, her boys play, and Imogen photographs them. CLICK. CLICK. CLICK. Photographing her sons leads Imogen to focus on the plants and flowers-- most notably her signature magnolia blossoms-- for which she will become known. "--Jacket flap.